Taxonomy of ’Euconnus complex’. Part IX. Problematic synonymy between Pycnophus and Nudatoconnus (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
The subgenus Nudatoconnus Franz of Euconnus Thomson was established for a group of Neotropical species, but later this name was placed as a junior synonym of Pycnophus Casey; the type species of the latter taxon is Nearctic. Examination of the type series of Scydmaenus rasus LeConte (type species of Pycnophus) and Euconnus sphaerocephalus Franz (type species of Nudatoconnus) revealed that both taxa share strikingly similar general appearance, especially the shape of the head and pronotum and largely reduced dorsal setae, and many taxonomically important structures that may justify the previously proposed synonymy. Differences are relatively minor (e.g., Sc. rasus lacks prosternal process, present as a narrow carina in E. sphaerocephalus), except for the shape of the mesoventral intercoxal process. In Sc. rasus, the process is typical as in Euconnus s. str. (and all remaining, previously studied subgenera of Euconnus), i.e., narrowly carinate and strongly elevated. In E. sphaerocephalus, however, the mesoventral process is strongly broadened and flattened ventrally. This unusual structure may justify not only removing Nudatoconnus from synonymy with Pycnophus, but even treating it as a separate genus. However, similarities in other structures between Sc. rasus and E. sphaerocephalus are so numerous that it seems unlikely that the two species are not closely related. More logical explanation is that the unusual form of the mesoventral process is derived from the typical narrow keel and has evolved as an autapomorphy of E. sphaerocephalus or a group of species related to the latter, possibly within Euconnus (Pycnophus). The synonymy is maintained, pending further study.